1967
DOI: 10.1677/joe.0.0390437
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in the Adenohypophysis of Pregnant and Lactating Rabbits

Abstract: Greatly enhanced secretory activity was observed during pregnancy and during lactation in the adenohypophysis ofthe rabbit, in cells similar to those designated type 1 in normal animals. These cells, whose granules were up to 550 m\g=m\ in diameter, showed, under the electron microscope, a very well developed ergastoplasm, an enlarged Golgi region, frequent nuclear inclusions and, during lactation, extensive degranulation. These observations, taken together with the evidence provided by light microscopy (Allan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 17 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Suggested cellular lineages of FS cells have included macrophage and glial cell lineages, but the actual lineage remains a matter of controversy (Coates and Doniach 1988;Young et al 1967;Kagayama 1965;Couly and Le Douarin 1985;VilaPorcile and Oliver 1984). In order to further elucidate the relationship between Ptx1 and individual hormones by localizing Ptx1 in the adult rat pituitary gland, we performed immunohistochemical analyses of Ptx1 and compared its localization with those of the anterior hormone-secreting cells and FS cells by double staining.…”
Section: Introductionmentioning
confidence: 99%
“…Suggested cellular lineages of FS cells have included macrophage and glial cell lineages, but the actual lineage remains a matter of controversy (Coates and Doniach 1988;Young et al 1967;Kagayama 1965;Couly and Le Douarin 1985;VilaPorcile and Oliver 1984). In order to further elucidate the relationship between Ptx1 and individual hormones by localizing Ptx1 in the adult rat pituitary gland, we performed immunohistochemical analyses of Ptx1 and compared its localization with those of the anterior hormone-secreting cells and FS cells by double staining.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and light and electron microscopic studies have shown that the changes are mostly due to the hyperplasia of prolactin cells (Young et al, 1967;Shiino et al, 1972;Merchant, 1974;Charlton and Worth, 1975;Hausler et al, 1978). Several authors have reported a close correspondence between the ultrastructural aspects of mammotropes and the stages of prolactin secretion (Hymer, 1961;Young et al, 1967;Shiino et al, 1972;Merchant-Larios and Mena, 1982).…”
mentioning
confidence: 99%
“…Biochemical and light and electron microscopic studies have shown that the changes are mostly due to the hyperplasia of prolactin cells (Young et al, 1967;Shiino et al, 1972;Merchant, 1974;Charlton and Worth, 1975;Hausler et al, 1978). Several authors have reported a close correspondence between the ultrastructural aspects of mammotropes and the stages of prolactin secretion (Hymer, 1961;Young et al, 1967;Shiino et al, 1972;Merchant-Larios and Mena, 1982). On the other hand little is known about the quantitative changes of the other anterior pituitary cell types, while definite variations of their hormone secretion are known to occur during lactation (Voogt et al, 1969;Amenomori et al, 1970;Sinha et al, 1974a,b;Smith, 1978;Taya and Greenwald, 1982).…”
mentioning
confidence: 99%
“…The peri卢 nuclear microfibrils seen in some granular cells in long-term cultures may have some association with disappearing ergastoplasm. Young, Foster & Cameron (1967) have pointed out that sedentary protein synthesized by free ribosomes may take the form of microfibrils.…”
Section: Discussionmentioning
confidence: 99%